Actualización de la colección de tipos del herbario MACB. - Carrasco de Salazar, María Andrea; Martín-blanco, Carlos José (Botanica Complutensis, 1998)
CARRASCO, M. A. & MARTÍN-BLANCO, C. 1. 1998. Type collection of MACH Herbarium update. BoL. CompJutensis, 22:173-178. In this paper the Type collection of the MACH Herbarium is updated. We indicate the category (Holotypus, lsotypus or Paratypus) of te specimens as well as te herbariums with other type specimens of the same taxa. The new Typus are: 6 Holotypus, 7 Isotypus and 3 Paratypus.